Expression of T-Bet, Eomesodermin, and GATA-3 Correlates With Distinct Phenotypes and Functional Properties in Porcine γδ T Cells - Rodríguez-Gómez, Irene M.; Talker, Stephanie C.; Käser, Tobias; Stadler, Maria; Reiter, Lisa; Ladinig, Andrea; Milburn, Jemma V.; Hammer, Sabine E.; Mair, Kerstin H.; Saalmüller, Armin; Gerner, Wilhelm (Frontiers in Immunology, 2019)
Unlike mice and humans, porcine γδ T cells represent a prominent subset of T cells in blood and secondary lymphatic organs. GATA-3, T-bet and Eomesodermin (Eomes) are transcription factors with crucial functions in T-cell development and functional differentiation, but their expression has not been investigated in porcine γδ T cells so far. We analyzed the expression of these transcription factors in γδ thymocytes, mature γδ T cells from blood, spleen, lymph nodes and lung tissue as well as in vitro stimulated γδ T cells on the protein level by flow cytometry. GATA-3 was present in more than 80% of all γδ-thymocytes. Extra-thymic CD2- γδ T cells expressed high levels of GATA-3 in all investigated organs and had a CD8α-/dimCD27+perforin- phenotype. T-bet expression was mainly found in a subset of CD2+ γδ T cells with an opposing CD8αhighCD27dim/-perforin+ phenotype. Eomes+ γδ T cells were also found within CD2+ γδ T cells but were heterogeneous in regard to expression of CD8α, CD27 and perforin. Eomes+ γδ T cells frequently co-expressed T-bet and dominated in the spleen. During aging, CD2-GATA-3+ γδ T cells strongly prevailed in young pigs up to an age of about two years but declined in older animals where CD2+T-bet+ γδ T cells became more prominent. Despite high GATA-3 expression levels, IL-4 production could not be found in γδ T cells by intracellular cytokine staining. Experiments with sorted and ConA + IL-2 + IL-12 + IL-18-stimulated CD2- γδ T cells showed that proliferating cells start expressing CD2 and T-bet, produce IFN-γ, but retain GATA-3 expression. In summary, our data suggest a role for GATA-3 in the development of γδ-thymocytes and in the function of peripheral CD2-CD8α-/dimCD27+perforin- γδ T cells. In contrast, T-bet expression appears to be restricted to terminal differentiation stages of CD2+ γδ T cells, frequently coinciding with perforin expression. The functional relevance of high GATA-3 expression levels in extra-thymic CD2- γδ T cells awaits further clarification. However, their unique phenotype suggests that they represent a thymus-derived separate lineage of γδ T cells in the pig for which currently no direct counterpart in rodents or humans has been described.